Functional significance of 8-isoprostanes in sinonasal disease and asthma. (August 2021) - Duchene, Brittany; Caffry, Sarah; Kaminsky, David A.; Que, Loretta G.; Poynter, Matthew E.; Dixon, Anne E.
Abstract: Background: The purpose of this study was to investigate how 8-isoprostanes, used as a marker of airway oxidative stress, were related to sinus disease and asthma. Methods: We analyzed samples and data from two separate studies, one investigating sinonasal disease in asthma, the other investigating the effect of BMI on airway disease. We measured airway (nasal lavage) 8-isoprostanes and investigated the relationship with measures of sinus and asthma symptoms, asthma control and lung function. Results: The study of people with sinonasal disease and poorly controlled asthma included 48 obese, 31 overweight and 23 lean participants. In multivariate analysis, nasal lavage 8-isoprostane levels increased with increasing BMI (p < 0.01), and were higher in Caucasian than African American participants (p = 0.01). Sinus symptoms were inversely related to nasal 8-isoprostanes (p = 0.02) independent of BMI and Race. In the study investigating the effect of BMI on airway disease, we enrolled 13 controls with obesity and 21 people with obesity and asthma: 8-isoprostane levels were higher in obese controls than in obese people with asthma (p < 0.01), and levels were inversely related to sinus symptoms (p = 0.02) and asthma control (p < 0.01). Interpretation: 8-isoprostanes in nasal lavage are increased in obesity, and increased in Caucasians compared with African Americans. However, levels are higher in obese controls than obese people with asthma, and appear inversely related to symptoms of airway disease. Clinical implication: Airway 8-isoprostanes likely reflect complex oxidative signaling pathways, which are altered in obesity and those of different race, rather than being a simple marker of airway oxidative injury. Capsule summary: Increased airway oxidative signaling (8-isoprostanes), may reflect normal physiology in the setting of obesity, as decreased levels are associated with disease activity in people with chronic sinonasal disease and asthma.